(untitled) (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
Character education is an important aspect that needs to be considered in the world of education. This study aims to determine the implementation of the Sari Satu program in developing the leadership spirit of fourth-grade students at Siwalan Elementary School. This study uses descriptive qualitative research. The research subjects were the principal, teachers, and fourth-grade students at Siwalan Elementary School. Research data were obtained from interviews, questionnaires, and observations. Data analysis techniques in this study consist of data reduction, data presentation, and conclusion drawing. The Sari Satu program is a short-term leadership rotation that provides students with the opportunity to take on the role and responsibility of a leader. This program is able to create a real-life simulation where students gain leadership skills that can be applied in life through direct experience. This is in accordance with the Javanese expression, namely Memayu Hayuning Bawana, Ambrasta dur Angkara. The meaning of this expression relates to the responsibility and role of a leader. "Memayu Hayuning Bawana" means striving to create prosperity and beauty in the world, while "Ambrasto dur Hangkoro" means eliminating all evil and injustice. The Sari Satu program effectively develops students’ leadership skills. Challenges within the program need to be addressed and solutions sought. The Sari program has the potential to be developed to shape a generation with character and leadership.